E-module development using problem-based learning approach to learn data processing in training students' critical thinking - Birnida Nurissamawati; Yuniawatika Yuniawatika; Siti Mas'ula (University of Muhammadiyah Malang, 2024)
The research conducted on data processing material in mathematics subjects at the elementary school level identified issues related to the low critical thinking skills of students. The study aimed to create e-modules based on the Problem Based Learning (PBL) model to enhance the critical thinking skills of grade VI students, ensuring validity, practicality, and effectiveness. This research uses the R&D method with the ADDIE model. The validity of the e-module is obtained from expert validation followed by two trials to obtain practicality, and effectiveness obtained from the test. The validity test of the e-module product obtained an average percentage of 92.56%, categorized as very valid. The practicality test obtained an average percentage of 90.39% categorized as very practical and the effectiveness results through normality gain obtained a percentage of 76.33% categorized as effective. Thus, the e-module product is declared valid, practical, and effective and affects critical thinking skills and improvement in learning outcomes. However, the study's limitation lies in the focus on data processing material, separate from thematic learning, suggesting future research should emphasize real-life problems and diverse content to maintain student engagement, alongside schools providing reliable internet access for teaching materials.